Dynamic Testing of Materials for Galvanising Pot Roll Bearings with Improved Performance - Giovanni Alparone (Materials, 2024)
Galvanising pot roll bearings are subjected to severe deterioration due to the corrosion of the bearing materials in liquid Zn, resulting in maintenance stops that can cost thousands of pounds per hour in downtime. Dynamic wear testing in molten Zn-Al and Zn-Al-Mg was conducted to assess the corrosion and wear resistance of three material pairs using a bespoke testing rig. The materials investigated in this study were Wallex6TM coated with WC-Co, stainless steel 316L coated with Al2O3, and as-received Wallex6TM and Wallex4TM alloys. It was found that only the Al2O3 coating remained unreactive in Zn alloy, whereas the materials containing Co were corroded, as evidenced by the formation of intermetallic compounds containing Al-Co-Zn-Fe. The results also highlighted that the dissolution of the Co matrix and diffusion of Zn and Al from the bath occurred in Wallex6TM and Wallex4TM. However, the diffusion of Zn into the WallexTM alloys was reduced by approximately 60% in the Zn-Al-Mg bath compared to Zn-Al. The wear scars were analysed to determine the wear coefficient of the worn specimens. Out of the three material couplings investigated in this study, minimal wear damage in both Zn-Al and Zn-Al-Mg was only obtained by pairing Wallex6TM with Al2O3 coatings.